Utilization of Waste Incineration Bottom Ash to Enhance Engineering Properties of Expansive Subgrade Soils - Damtew Tsige Melese (Advances in Civil Engineering)
Expansive soils are a type of soil that exhibits the ability to swell and shrink with the variation of moisture content. Lightweight structures such as pavements, sidewalks, and driveways face failures due to the swelling and shrinkage behavior of expansive soils. Therefore, the aim of this study is to investigate the effect of waste incineration bottom ash on the engineering properties of expansive subgrade soils. To investigate the waste incineration bottom ash, tests such as specific gravity, Atterberg limit, free swell test, compaction characteristics, unconfined compression strength, and Californian bearing ratio (CBR) were conducted. The soil was stabilized by waste incineration bottom ash with proportions of 10%, 15%, 20%, 25%, and 30% by dry weight. From the laboratory test results, the soil under this category has poor engineering properties which include high plastic index, high free swell index, low UCS, and low CBR. The performance of soil improved as waste incineration bottom ash content increased with respect to curing time. The curing time of the sample has a significant effect on the performance of the weak subgrade soil.